Avaliação da produção de biodiesel segundo os princípios da engenharia da sustentabilidade - Ferracini, Ana Rachel Bernardi (Universidade Federal de São Carlos, 2021)
Two of the main activities responsible for the environmental impacts globally are energy production and chemical industries, largely due to the burning of fuels and the handling of polluting or health-damaging chemical residues. Within this scenario, in 1991, the concept of green chemistry was introduced, a science that studies to reduce or eliminate the use and generation of hazardous substances in the development of chemical products and processes. One of its aspects in focus is to increase the efficiency of the processes, to try to produce less impurities, and to minimize energy consumption. Linked to this panorama, the growth of sustainable development in global forums reiterates the importance of actions aimed at the economic, social and environmental pillars to meet the needs of society without harming the future of the planet. Sustainable engineering uses the principles of sustainability to implement routes and solutions with a long-term vision throughout the entire lifecycle. This work has as main objective to evaluate the biodiesel production process with the principles of sustainable engineering, approaching concepts and analyzing data obtained through systems engineering tools in processes. In the case study of the related work, the biodiesel production process produced by palm oil was simulated using the ASPEN Plus V11® process simulation software. Another tool, WAste Reduction algorithm (WAR algorithm) was used in order to provide relevant data for analysis and application in the development of the process in question. The results found showed that small variations carried out in a process to achieve greater energy efficiency or yield, can directly result in environmental impacts and, therefore, affect the analysis of the product's life cycle. It was also seen that, for the theme to be fully implemented and have a greater role in society, it needs to be introduced already in the training of new professionals, to bring changes and sustainable solutions along their personal and professional path.
Evaluation of biodiesel production according to the principles of sustainability engineering
Keywords: Process development; WAR algorithm; Sustainable Engineering; Biodiesel; Desenvolvimento de processo; WAR algorithm; Engenharia sustentável; ENGENHARIAS::ENGENHARIA QUIMICA